FEATURES OF CREATIVE TASKS AND EXERCISES FORMATION OF STUDENTS 'CREATIVE ACTIVITY (Pedagogy of Higher and Secondary Education, 2022)
The peculiarities of the creative exercises, which are used at the second level of the formation of the pupil's creative work at the music lessons are opening in this article.